Discrimination: a health hazard for people from refugee and asylum-seeking backgrounds resettled in Australia - Anna Ziersch; Clemence Due; Moira Walsh (BMC, 2020)
Abstract Background Research has shown that discrimination is harmful to health, but there is relatively little known about discrimination experienced by people from refugee and asylum-seeking backgrounds in resettlement countries and associated health effects. This qualitative-focused mixed methods paper reports on discrimination experienced by refugees and asylum seekers, responses to discrimination, and impacts on health. Methods As part of a broader study of housing, social inclusion and health, surveys were completed by 423 adult refugees and asylum seekers living in South Australia who had been in Australia for up to 7 years. The survey included questions on discrimination based on skin colour, ethnicity and religion, as well as questions on hope, trust, belonging, sense of control and health (including the SF-8). Semi-structured interviews were conducted with 65 survey participants, purposively sampled by visa status, continent and gender, further exploring experiences of discrimination. These and survey open-ended responses were analysed thematically. Results Twenty-two percent of survey participants reported experiences of discrimination since arriving in Australia (14% in the last year), and 90% of these felt that discrimination had harmed their health. Key settings of discrimination were public transport, within the neighbourhood, and in relation to employment. Those who reported discrimination had significantly worse mental health (p < .000) but not physical health. Discrimination was also associated with less sense of belonging (p = .001), lower levels of trust (p = .038), reduced sense of control (p = .012) and less hope (p = .006). Incidents described in interviews and the open-ended survey responses included incivility, physical assault, and denial of services, experienced across intersecting characteristics of race/ethnicity, religion, gender and visa status. Responses to discrimination spanned affective, cognitive and behavioural dimensions, ranging across types of experience, participant characteristics and context, with most individuals reporting multiple response types. While some of the responses were reported by participants as protective of health, participants' reflections indicated significant negative impacts on mental health in particular. Conclusion Discrimination featured in the resettlement experiences of a significant number of refugees and asylum seekers, with participants reporting clear negative impacts on mental health. Addressing discrimination is a key resettlement and health issue requiring urgent action.